INCOME EXPECTATION, ENTREPRENEURSHIP EDUCATION AND ENTREPRENEURIAL INTEREST: TESTING THEIR RELATIONSHIPS - Maryati, Tri; Setiarto, Erwan (The journal of contemporary issues in business and government, 2021)
This empirical study discusses the factors that cause students' interest in entrepreneurship and examines the differences in the factors that generate interest in entrepreneurship in management students at Universitas Negeri Yogyakarta and Universitas Muhammadiyah Yogyakarta. In this empirical study the number of respondents was 125 people. The sampling technique was purposive sampling, namely students who had attended entrepreneurship courses and had attended entrepreneurship seminars. The data analysis tool uses multiple regression with SPSS software. The results of data analysis indicate that the student's interest in entrepreneurship is affected by entrepreneurship education and income expectations with positive and significanteffect. In addition, there are significant differences in responses about income expectations, entrepreneurship education, and interest in entrepreneurship in Management students of UNY and UMY Management students.